HUBUNGAN ANTARA DISIPLIN BELAJAR DAN PERSEPSI SISWA TERHADAP PENGGUNAAN MEDIA CD INTERAKTIF DENGAN HASIL BELAJAR MATEMATIKA - Jumaroh Na; Lisna Marwani (Akademika, 2016)
This research aims to find out whether there is a meaningful relationship between thedisciplines of study and student perceptions of the use of the interactive CD media together withthe results of learning math grade V SDN in Bekasi. Research methods used are reasonable, andthe population survey as much as 310 students. The sampling techniques used simple randomsampling as much amount. with 76 students.The results of this research were obtained: (1) there is a positive relationship between thedisciplines of study with the results of the learning of mathematics, (2) there is a positiverelationship between students ' perceptions towards the use of interactive CD media with theresults of the learning of mathematics, (3) there is a positive relationship between the disciplinesof study and student perceptions of the use of the media the CD together with the results of thelearning of mathematics.Thus summed up the discipline of study and student perceptions of the use of theinteractive CD media that high increase results learn math students